Perinatal HIV-1 transmission: Fc gamma receptor variability associates with maternal infectiousness and infant susceptibility. Issue 1 (December 2016) - Lassaunière, Ria; Musekiwa, Alfred; Gray, Glenda; Kuhn, Louise; Tiemessen, Caroline
Abstract Background Accumulating data suggest that immune effector functions mediated through the Fc portion of HIV-1-specific immunoglobulin G (IgG) are a key component of HIV-1 protective immunity, affecting both disease progression and HIV-1 acquisition. Through studying Fc gamma receptor (FcγR) variants known to alter IgG Fc-mediated immune responses, we indirectly assessed the role of FcγR-mediated effector functions in modulating perinatal HIV-1 transmission risk. In this study, genotypic data from 79 HIV-1 infected mothers and 78 HIV-1 infected infants (transmitting cases) were compared to 234 HIV-1 infected mothers and 235 HIV-1 exposed-uninfected infants (non-transmitting controls). Associations, unadjusted and adjusted for multiple comparisons, were assessed for overall transmission and according to mode of transmission—intrapartum (n = 31), in utero (n = 20), in utero-enriched (n = 48). Results The maternal FcγRIIIa-158V allele that confers enhanced antibody binding affinity and antibody-dependent cellular cytotoxicity capacity significantly associated with reduced HIV-1 transmission [odds ratio (OR) 0.47, 95 % confidence interval (CI) 0.28–0.79, P = 0.004; PBonf > 0.05]. In particular, the FcγRIIIa-158V allele was underrepresented in the in utero transmitting group (P = 0.048; PBonf > 0.05) and in utero-enriched transmitting groups (P = 0.0001; PBonf < 0.01). In both mother and infant, possession of an FcγRIIIb-HNA1b allotype that reduces neutrophil-mediated effector functions associated with increased transmission (OR 1.87, 95 % CI 1.08–3.21, P = 0.025; PBonf > 0.05) and acquisition (OR 1.91, 95 % CI 1.11–3.30, P = 0.020; PBonf > 0.05), respectively. Conversely, the infant FcγRIIIb-HNA1a|1a genotype was significantly protective of perinatal HIV-1 acquisition (OR 0.42, 95 % CI 0.18–0.96, P = 0.040; PBonf > 0.05). Conclusions The findings of this study suggest a potential role for FcγR-mediated effector functions in perinatal HIV-1 transmission. However, future studies are required to validate the findings of this study, in particular associations that did not retain significance after adjustment for multiple comparisons.